Black metal, trauma, subjectivity and sound : screaming the abyss - Shadrack, Jasmine Hazel (Emerald Publishing Limited, 2020)
Black Metal, Trauma, Subjectivity and Sound: Screaming the Abyss weaves together trauma, black metal performance and disability into a story of both pain and freedom. Drawing on her years as a black metal guitarist, Jasmine Hazel Shadrack uses autoethnography to explore her own experiences of gender-based violence, misogyny, and the healing power of performance. This profoundly personal book offers a detailed explanation of autoethnography, followed by a careful exposition of the relationship between metal and gender, considering - among other things - how women are engaged with by metal music culture. After examining the various waves of black metal and how this has impacted black metal theory, the book moves on to consider female performers and performance as catharsis, including a discussion of the author's work as guitarist and vocalist with the black metal band Denigrata and her alter-ego, the 'antlered priestess' Denigrata Herself. The book concludes with some thoughts on acquired disability, freedom and peace. The book includes a foreword from eminent gender researcher Rosemary Lucy Hill, a guest section from metal scholar Amanda DiGioia, an epilogue from Rebecca Lamont-Jiggens (a legal pracademic specialising in disability), suggestions of sources of help for those in abusive relationships and further reading for those wishing to learn more about black metal theory.
Keywords: Shadrack, Jasmine Hazel.; Black metal (Music) -- Social aspects.; Misogyny.; Disabilities.; Psychic trauma.; Music -- Health aspects.; Music, Genres & Styles, Heavy Metal.; Heavy Metal music.; elektronické knihy; electronic books